The Transformation of Intracranial Subdural Hygroma to Chronic Subdural Hematoma Following Endoscopic Spinal Surgery: A Case Report - Lin, Guang-Xun; Chen, Chien-Min; Kim, Jin-Sung; Song, Kwan-Su (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background We present the case of an intracranial subdural hygroma resulting from intraoperatively undetected dural tear after unilateral biportal endoscopic (UBE) spine surgery for lumbar spinal stenosis.Case Description An 80-year-old woman presented with insidious onset, gradually progressing low back pain, and right leg pain of 1-year duration. The pain radiated to the right L4–L5 dermatomes. Neurogenic intermittent claudication was <300 m. Motor function was normal. Lumbar magnetic resonance imaging showed a lateral recess stenosis at the L3–L4 and L4–L5 levels. These lesions were operated on by the UBE decompression technique.No major complications were encountered during the operation. But soon we found out that there was an undiscovered dura tear. We placed the patient under close observation for 2 weeks. After 30 days, we confirmed that subdural hygroma had changed to chronic subdural hematoma. Conservative treatment was continued. On postoperative day 90), the condition was stable and the symptoms improved completely.Conclusions We concluded that a spinal cerebrospinal fluid leakage can result in an intracranial subdural hygroma. Intracranial subdural hygromas and hematomas after lumbar spinal surgery should be cautiously assessed and treated.
Keywords: dural tear; subdural hygroma; endoscopic spinal surgery; complication; subdural hematoma